2016
DOI: 10.1177/1477153515578309
|View full text |Cite
|
Sign up to set email alerts
|

A suitable and energy-efficient luminous environment for a shared office

Abstract: This paper aims to identify suitable and energy-efficient luminous environments for two users sharing the same office and conducting various activities at the same time (paper and/or computer-based work, meeting with a visitor). The office is lit by daylight, controlled by an exterior shading system and by artificial light, composed of ceiling sources and a task lamp on each desk. In all, 930 subjects participated in six psychophysical tests conducted on the internet, each dedicated to a user position and an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The WELL Building Standard TM was developed to further this agenda by being specifically focused on the health outcomes of the SASBE 12,1 building designs, policies and operational decisions of the building. This thus required the ongoing evaluation of both the environmental performance and occupant experiences postoccupancy (Villa and Labayrade, 2015).…”
Section: Enablers Of Ieq Principlesmentioning
confidence: 99%
“…The WELL Building Standard TM was developed to further this agenda by being specifically focused on the health outcomes of the SASBE 12,1 building designs, policies and operational decisions of the building. This thus required the ongoing evaluation of both the environmental performance and occupant experiences postoccupancy (Villa and Labayrade, 2015).…”
Section: Enablers Of Ieq Principlesmentioning
confidence: 99%
“…Dissatisfaction with light quality was mainly caused by glare, and when the glazed percentage was under 40%, people felt comfortable in their workplaces (Menzies & Wherrett, 2005). A research of Villa and Labayrade (2016) aiming for energy-efficient luminous environment identified an optimal solution to be suitable for different user requirements. In shared office spaces, the solution is to supply an individual task lamp that does not have a high-power demand (11W each, LED lighting).…”
Section: Light and Daylightmentioning
confidence: 99%
“…Dissatisfaction with light quality was mainly caused by glare, and when the glazed percentage was under 40 per cent, people felt comfortable in their workplaces (Menzies and Wherrett, 2005). A research of Villa and Labayrade (2016) aiming for energy-efficient luminous environment identified an optimal solution to be suitable for different user requirements. In shared office spaces, the solution is to supply an individual task lamp that does not have a high-power demand (11 W each, LED lighting).…”
Section: Literature Reviewmentioning
confidence: 99%